The Relationship between Work Motivation and Nurse Performance at 'Aisyiyah Bojonegoro Hospital - Siti Ulfiana; Lilis Maghfuroh; Tjatur Ermitajani Judi; M. Arif Saifuddin; Nahardian Vica Rahmawati; Dadang Kusbiantoro (Jurnal Surya, 2024)
Introduction: Motivation can encourage a person to behave in order to achieve goals. The magnitude of motivation depends on each individual. If an employee has high work motivation, the resulting performance will increase. Based on the results of the initial survey, the causative factor is because the incentives received compared to the work done are not worth it, causing a decrease in morale. The purpose of the study was to determine the relationship between work motivation and the performance of nurses at 'Aisyiyah Bojonegoro Hospital. Methods: The research design used correlation analytics with the Cross Sectional design. The research sample was 61 nurses using the Proportionate Stratified Random Sampling technique. The independent variable is work motivation and the dependent variable is performance. Data collection using questionnaires. Results: : The study obtained the results of most nurses who have good work motivation as many as 39 nurses (63.9%), most of the 35 nurses have good performance with a percentage of 57.4% data processing using the SPSS 27 for windows program obtained a value of 0.000 or with a significant value (p value< 0.05) which means that there is a relationship between work motivation and nurse performance at 'Aisyiyah Bojonegoro Hospital. The results of the spearman rank test obtained a correlation coefficient value = 0.595 which means the level of strength of the relationship between 2 moderate variables. Conclusion: The conclusion of this study is that there is a relationship between work motivation and nurse performance, and it is hoped that hospitals will further increase nurses' work motivation so that the resulting performance will also increase. Keywords: Health worker, Knowledge, Occupational Health and Safety (K3)